IMPROVEMENT OF THE SECURITIES SETTLEMENT SYSTEM IN THE EUROPEAN UNION - D. Jurevičienė; M. Borovikova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The financial crisis and recession in Europe have made it necessary to improve the system of regulation of the stock market, including the settlement of securities transactions. The paper constitutes the existing features of securities settlement in the stock markets of the EU and presents the measures and proposals to improve the settlement of securities transactions.